2021
DOI: 10.1002/zaac.202100003
|View full text |Cite
|
Sign up to set email alerts
|

Three new Cd(II)/Zn(II) coordination polymers assembled via dual‐ligand strategy: crystal structures and luminescent properties

Abstract: Dual-ligand strategy was used to synthesize three new coordination polymers with the formula as [Cd(HL(3) (H 3 L = biphenyl-3,4',5-tricarboxylic acid, 2,2'-bipy = 2, 2'-bipyridine, bib = 1,4-bis(imidazol-1-yl)butane), which were further structurally characterized by single crystal X-ray diffraction analyses. Compound 1 features a 1D infinite chain structure and π…π interactions between adjacent 1D chains gives rise to a 2D layer and further OÀ H…O hydrogen bonding interactions between adjacent 2D layers afford… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…It is well-known that CPs constructed with a d 10 metal center and conjugated organic linkers are promising candidates for photoactive materials, [23][24][25][26][27] with potential applications such as chemical sensors and electro-luminescent materials. Therefore, the photoluminescence (PL) properties of the three complexes, together with the free ligands, are investigated at room temperature for comparison (Figure 7).…”
Section: Luminescent Propertiesmentioning
confidence: 99%
“…It is well-known that CPs constructed with a d 10 metal center and conjugated organic linkers are promising candidates for photoactive materials, [23][24][25][26][27] with potential applications such as chemical sensors and electro-luminescent materials. Therefore, the photoluminescence (PL) properties of the three complexes, together with the free ligands, are investigated at room temperature for comparison (Figure 7).…”
Section: Luminescent Propertiesmentioning
confidence: 99%
“…The transition metals zinc and cadmium are in the same main group (IIB) on the periodic table and have completely filled d orbitals and two s electrons in the outermost shell. Compared with zinc, cadmium (a metal element) has a richer coordination behavior and more geometrical configurations; moreover, cadmium complexes have excellent optical properties [29,[38][39][40][41][42][43][44][45][46][47][48][49]. To further investigate the structure and properties of adenine and cadmium complexes, in this study, we designed and synthesized two new three-dimensional organic-inorganic hybrid crystalline materials, namely, [(C 5 H 6 N 5 ) 2 CdCl 4 ] (1), with the abbreviated formula [Ade-Cl], and [(C 5 H 6 N 5 ) 2 CdBr 4 ] (2) with the abbreviated formula [Ade-Br].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] It is well known that low-dimensional hybrid lead halides readily exhibit broadband white-light emissions with high color rendering indices and PLQYs mainly deriving from the strong electron-phonon coupling effect in soft and distorted crystal lattice. [18][19][20] Previous experimental and theoretical studies demonstrated that lowering the structural dimensionality is positively related to stronger quantum confinement effect, which effectively reduce the width of the quantum well and increase the exciton binding energy resulting in stronger broadband white-light emission. [21][22][23] Undoubtedly, the bond characteristics of inorganic skeletons crucially determine the band structures of hybrids, which plays a very important function in determining the excited state energy and PL properties.…”
Section: Introductionmentioning
confidence: 99%